La conformità della volontà umana con quella divina nella Somma Teologica di San Tommaso d’Aquino (seconda parte) - Mestre, L.C., Alberto (Alpha Omega, 2020)
Summary: In what way can the human will be conformed with the divine Will? That is the subject of this article. The inquiry focuses primarily on St. Thomas Aquinas’ Summa Theologiae, Ia-IIae, quaestio 19, a question that specifically concerns the subject from a moral perspective. Is it possible that man would dare to make such a claim? If it is possible, how could it be brought about? The article traces the footsteps of St. Thomas, who faces this problem, well aware of the enormous importance it represents, and also aware that we stand before one of the greatest mysteries of human and Christian life. Key Words: conformity, Will of God, Will of the Father, obedience, self-abandonment to the divine will. Parole chiave: conformità, Volontà di Dio, Volontà del Padre, obbedienza, abbandono alla Volontà divina. <iframe class="ginger-extension-definitionpopup" style="left: -80.3472px; top: -103.785px; z-index: 100001; display: none;" src="chrome-extension://kdfieneakcjfaiglcfcgkidlkmlijjnh/content/popups/definitionPopup/index.html?title=Summary&description=a%20brief%20statement%20that%20presents%20the%20main%20points%20in%20a%20concise%20form">